2007
DOI: 10.1016/j.ijdevneu.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Early maturation of GABAergic synapses in mouse retinal ganglion cells

Abstract: This study was aimed to characterize the earliest phases of synapse development in mouse retinal ganglion cells (RGCs) by recording spontaneous postsynaptic currents (PSCs). First PSCs were detected at embryonic day 17 and completely suppressed by bicuculline, demonstrating their GABAergic nature. Starting from postnatal day 3 a small fraction of RGCs had rapidly decaying, most likely glutamatergic currents. The present results suggest that functional GABAergic synapses with RGCs appear before birth and that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, ribbon synapses, characteristic of bipolar cells, are not present until P11, after which they also increase at an equivalent rate [18]. Indeed, functional drive from amacrine cells develops prior to glutamatergic transmission from bipolar cells [55]. Our previous studies separately mapping excitatory and inhibitory postsynaptic sites on individual RGCs also suggested that inhibitory and excitatory synaptogenesis may be coordinated during development to balance inhibition and excitation after glutamatergic synaptogenesis begins, at least for one RGC type [15], [26].…”
Section: Discussionmentioning
confidence: 92%
“…However, ribbon synapses, characteristic of bipolar cells, are not present until P11, after which they also increase at an equivalent rate [18]. Indeed, functional drive from amacrine cells develops prior to glutamatergic transmission from bipolar cells [55]. Our previous studies separately mapping excitatory and inhibitory postsynaptic sites on individual RGCs also suggested that inhibitory and excitatory synaptogenesis may be coordinated during development to balance inhibition and excitation after glutamatergic synaptogenesis begins, at least for one RGC type [15], [26].…”
Section: Discussionmentioning
confidence: 92%
“…For example, in the hippocampus, the apical dendrite of CA1 pyramidal cells is first contacted by GABAergic inteneurons prior to extension of these dendrites into the stratum lacunosum-moleculare, where they later receive input from glutamatergic afferents of the perforant pathway [4,5]. Likewise, RGCs also obtain GABAergic and glycinergic drive from amacrine cells prior to the formation of glutamatergic synapses from bipolar cells [51] (but see [52]). Unlike hippocampal pyramidal cells where dendrites need to reach available glutamatergic afferents, the delay in glutamatergic synaptogenesis onto RGCs is because bipolar cells are generated much later than amacrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both GABA and glycine are already localized within neurons at the time of birth in rodent retina, whereas expression of glutamate appears diffuse around birth until about a week after birth (Fletcher and Kalloniatis, 1997). GABA A -specific spontaneous postsynaptic currents can be recorded from retinal ganglion cells as early as embryonic day 17 (Unsoeld et al, 2008). Spontaneous excitatory postsynaptic currents (EPSCs), on the other hand, can be recorded from mouse retinal ganglion cells only around P7 (Johnson et al, 2003; Morgan et al, 2008).…”
Section: Synapse Structure and Connectivity Of Retinal Neuronsmentioning
confidence: 99%